Sociologia e espírito do mamulengo: ensinando e aprendendo com a arte do fantoche - Xavier, Lisimére Cordeiro do Vale (2024)
This work presents a Digital Paradidactic Pedagogical Guide entitled "Sociology and Spirit of the Mamulengo: Teaching and Learning with the Art of the Puppet". The main objective is to explore, at the interface between school knowledge, science and popular culture, the possibility of teaching and learning Sociology through the art of mamulengo, with emphasis on the work of Pedro Boca Rica, a renowned master of this art in the State of Ceará, in the city of Ocara. Puppets, protagonists of his work and this proposal, are used as pedagogical tools to illustrate, dialogue and understand, by alternative means, fundamental categories of sociology. The characters and conflicts of the dramas dramatized by the mamulengo allow us to establish relationships with some contents and concepts such as the individual, society, domination and power presented by the theorists Èmile Durkheim, Karl Marx, Pierre Bourdieu and, above all, Max Weber, with their ideal types, which express social reality, especially those used to understand the dynamics of power and domination. Among the various characters of Pedro Boca Rica's mamulengo culture, some iconic puppets stand out: the Colonel, the Baltazar, the Cassimiro Coco, the Mané Fuzarca de Breu, the Maneiro-Pau, the Astrogilda, the Barbudo, the Delegate Inácio da Catingueira and the Fuleragem who in a dynamic way increase the instruments, tools, digital technological resources and activities proposed in the Guide. Characters represented by Mané Fuzarca de Breu, Maneiro-Pau and Astrogilda represent the social empowerment of the individual and the northeastern society locus of expression and strength of the popular culture of the art of accordion, forró, quadrilha and June festivals, giving them a surplus; cultural, social, political, economic and educational extraordinary. Characters such as; Fuleragem, Baltazar and Casimiro Coco embrace the struggle and resistance Against the exploitation, abuses and injustices practiced by the oligarchic elites in Brazilian Society throughout history. The pedagogical material developed was tested and evaluated by fellow teachers as a way to check its applicability in the educational context.